การผลิตมันฝรั่งแผ่นทอดกรอบแบบขึ้นรูป - สุดารัตน์ พริกบุญจันทร์ (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
This research involved studies on formulation and processing in order to obtain a good quality and consumer-acceptable restructured potato-chips product. Initially, analyses of proximate composition of raw materiais viz, potato flake, potato starch and corn starch were conducted. The results showed that they contained 81.04, 79.71 and 87.3% of carbohydrate and 9.16, 0.10 and 1.60% of protein respectively. Only a small amount of fat, fiber and ash content were found in these raw materials. For formulation study, potato flake, potato starch and corn starch were varied at 60-80% and 5.20% respectively for potato chips making. The appropriate prototype product was found to be composed of 33.04% potato flake and 7.08% each of potato starch and corn starch. In the processing of potato chips, partial of potato dough sheet was first studied. The thin dough sheet was dried at 35, 40 and 45℃ for 90, 105 and 120 minutes in comparison with drying at room temperature for 3 hours and those without partial dehydration prior to frying. Drying at 450C for 90 minutes gave a crisp and good- color product with low moisture both before and after frying. The subsequent experiment involved study of frying of frying temperature by varying frying temperatures at 185 and 190℃ for 10, 12 and 14 seconds. It was shown that frying at 190℃ for 12 seconds gave a product with best sensory quality. For addition of flavoring agents, BBQ flavor was shown to be the most accepted among 4 types of flavor agents tested i.e. chicken, Tomyam, Patkrapow and BBQ. The proximate composition of the final product was: moisture 3.72% protein 11.38%, fat 28.07%, fiber 0.06%, and carbohydrate 56.25% while the color, hardness and water activity were L=69.21, a=3.71, b=25.86 g-force and aw = 0.289. Microbiological tests yielded less than 100 and 10 TPC and e=yeast and mold count respectively. Products packed in OPP /PE/ metallized PET / CPP pouches had a shelf life of about 6 weeks at 30℃.